Posterior Cruciate Ligament Revision Surgery: Outcomes, Failure Rates, and Complications: A Systematic Review of the Literature - D'Ambrosi, Riccardo; Carrozzo, Alessandro; Di Feo, Fabrizio; Skopljak, Edna; Kambhampati, Srinivas B. S.; Attri, Manish; Meena, Amit (The Journal of Knee Surgery, 2025)
To synthesize and qualitatively assess the currently available evidence in the literature regarding the revision of posterior cruciate ligament (PCL) reconstruction. A systematic review was conducted on the basis of the preferred reporting items for systematic reviews and meta-analyses guidelines. The outcome data extracted from the studies were the Lysholm score, Orthopadische Arbeitsgruppe Knie (OAK) scoring system, KT-2000, International Knee Documentation Committee (IKDC) subjective and objective, radiological changes, rate of return to sports, complications, and failures and/or revision surgeries. The cohort consisted of 54 patients (42 [77.8%] men and 12 [22.2%] women), with a mean age of 33.14 ± 3.67 years (range: 17–48 years). The mean postoperative follow-up was 71.8 ± 45.32 months, whereas the mean time from primary surgery to revision was 41.7 ± 4.5 months. All studies reported a clinical improvement from preoperative to final follow-up in terms of the Lysholm, OAK, KT-2000, and IKDC scores (p < 0.05). Posterior displacement was significantly improved in all studies, demonstrating the stability of the knee. The mean posterior displacement ranged from a preoperative value of 10.68 ± 0.7 mm to a final value of 2.7 ± 0.2 mm (p < 0.05). A total of two (3.7%) failures were reported, and there were also eight (14.8%) revision surgeries. Studies on PCL reconstruction revisions have shown satisfactory clinical outcomes and a high level of knee stability, with minimal risk of new reruptures. However, the rate of returning to preinjury sports activity is relatively low. Whenever possible, it is recommended to perform the ligament revision in a single stage. The level of evidence is a systematic review of level IV.
Keywords: posterior cruciate ligament; revision surgery; sports medicine; arthroscopy